Role of Dkk3 protein in regulation of lymphocyte cytotoxicity: systematic review - Strakh, Alena; Vialichka, Alesia; Nizheharodava, Darya; Zafranskaya, Marina (Journal of the Belarusian State University. Ecology, 2025)
The study of the role of the Dkk 3 protein in the regulation of lymphocyte cytotoxicity is an urgent, little-studied area in science. It is an extremely difficult task for researchers to understand the molecular and genetic aspects of the functioning of this protein, as well as to identify the relationship between Dkk3 and the human immune system. The Dickkopf protein family is diverse and includes five proteins. Dkk3 interacts with the Wnt signaling pathway, which distinguishes this protein from other Dkk members. In addition, Dkk3 has a variety of biological roles (prevents cardiac hypertrophy and promotes stem cell differentiation). This protein can act as a modulator of the immune system. Dkk3 plays an important role in establishing peripheral tolerance of T cells. This paper provides a systematic review of scientific publications in the PubMed database devoted to the study of the role of Dkk3 in the regulation of lymphocyte cytotoxicity, published from 2020 to 2025. During the systematic review, 182 sources were studied, from which 41 articles included in the study were selected during the screening process. The search queries and keywords contained «Dkk3 as an extracellular antagonist of Wnt», «regulatory pathways through Dkk3», «tumor suppressor gene», «oncogene», «relationship of Dkk3 with a subpopulation of lymphocytes», «cytotoxic lymphocytes». A systematic review will expand the field of research on the biological role of Dkk3, in particular on the role of Dkk3 in regulating lymphocyte cytotoxicity, for further study and discovery of new directions on this research topic.